Results of models testing of cross-polarization discrimination and co-polar attenuation due to rain - Ельченко, Сергей Владимирович (Eastern-European Journal of Enterprise Technologies, 2011)
The present article considers the results of testing of models describing the correlation between cross-polarization discrimination and co-polar attenuation due to rain